Effects of a Pulmonary Rehabilitation Program With Balance Training on Patients With COPD. Issue 2 (March 2015) - Marques, Alda; Jácome, Cristina; Cruz, Joana; Gabriel, Raquel; Figueiredo, Daniela
Abstract : PURPOSE: Patients with chronic obstructive pulmonary disease (COPD) have balance impairments. However, pulmonary rehabilitation (PR) is associated with only minor improvements in functional balance. Therefore, there is a need to explore the role of balance training within PR. This study aimed at assessing the effects of a PR program, with a specific component of balance training, on functional balance of patients with COPD. METHODS: Outpatients with COPD (N = 22, age = 68.0 ± 11.8 years; forced expiratory volume in 1 second = 72.2 ± 22.3% predicted) participated in a 12-week PR program including exercise training and psychosocial support and education. Exercise training sessions comprised endurance, strength, and a specific component of balance training. The Timed Up and Go (TUG) test was used to assess functional balance before and after the PR. Health-related quality of life (St George's Respiratory Questionnaire), quadriceps muscle strength (10 repetition maximum), and exercise tolerance (6-minute walk test) were also assessed. RESULTS: Patients demonstrated significant improvements in TUG scores after PR (mean change −1.7 ± 1.4 seconds; P = .001; effect size = 1.249). Before PR, 9 (41%) participants and after PR only 1 (4.5%) participant had a TUG performance worse than the average performance of age-matched healthy peers ( P = .008). The St George's Respiratory Questionnaire symptoms score ( P = .012), quadriceps muscle strength ( P = .001), and exercise tolerance ( P = .001) were also improved. CONCLUSIONS: Pulmonary rehabilitation with a specific component of balance training had a large effect on functional balance in patients with COPD. Findings highlight the value of including balance training in PR programs. Further research is needed to determine the optimal intervention to improve balance and its specific components among patients with COPD. Abstract : This study assessed the effects of a pulmonary rehabilitation program, including a specific balance training component, in patients with chronic obstructive pulmonary disease. Results suggest that this additional component effectively impacted functional balance. Further research is needed to determine the optimal approach for improving balance.